A multifaceted role for MOF histone modifying factor in genome maintenance. (January 2017) - Mujoo, Kalpana; Hunt, Clayton R.; Horikoshi, Nobuo; Pandita, Tej K.
Highlights: MOF acetylates lysine 16 of histone H4 (H4K16ac) and plays a role in transcription and the DNA damage response. MOF interacts with a range of proteins that extend its potential significance well beyond transcription and DNA damage repair. MOF affects ATM (ataxia-telangiectasia mutated) function and ATM-dependent MOF post-translational modification regulates DNA DSB pathway choice. MOF is essential for embryonic development as well as post-mitotic and non-dividing cell survival. MOF is critical for stem cell-renewal and pluripotency. Abstract: MOF (males absent on the first) was initially identified as a dosage compensation factor in Drosophila that acetylates lysine 16 of histone H4 (H4K16ac) and increased gene transcription from the single copy male X-chromosome. In humans, however, the ortholog of Drosophila MOF has been shown to interact with a range of proteins that extend its potential significance well beyond transcription. For example, recent results indicate MOF is an upstream regulator of the ATM (ataxia-telangiectasia mutated) protein, the loss of which is responsible for ataxia telangiectasia (AT). ATM is a key regulatory kinase that interacts with and phosphorylates multiple substrates that influence critical, cell-cycle control and DNA damage repair pathways in addition to other pathways. Thus, directly or indirectly, MOF may be involved in a wide range of cellular functions. This review will focus on the contribution of MOF to cellular DNA repair and new results that are beginning to examine the in vivo physiological role of MOF.